Singularities in using Vic-3D™ Digital Image Correlation software and its application to the study of inelastic strain fields - Tretyakova, Tatiana Viktorovna (Computational Continuum Mechanics, 2014)
The present paper deals with the numerical processing of experimental data recorded by the Vic-3D digital image correlation measurement system, which provides estimation of the strain fields in the tension tests of flat Al-Mg alloy specimens. The influence of the subset and the step size selection on the inelastic strain field configuration has been studied by the algorithms for motion estimation in successive images. It is shown that these parameters have different effects on the accuracy of the digital image correlation analysis, the size of the marginal zone and the refinement of the strain fields. The paper contains the results of estimation of inhomogeneous strain fields due to the Portevin-Le Chatelier effect in the tension tests of the Al-Mg alloy flat specimens obtained using the Vic-3D digital image correlation measurement system.
Keywords: aluminum-magnesium alloy; Lüder’s deformation; jerky flow; Portevin-Le Chatelier effect; digital image correlation; optimization criteria for pattern matching; strain field